Richard Wagner, Destiny and Fulfilment Tannhäuser or the Capitalisation on Medieval Legends - George Hariton (Anastasis: Research in Medieval Culture and Art, 2020)
To speak nowadays of Wagner’s egotism, after time has “classified” his incontestable œuvre in the highest areas of international dramaturgy, is not in the least surprising. To notice, however, his sparks of genius and the radical anticipations announced as early as his first operas, this is truly impressive with a musician who had discovered the art of handling sounds so late. The key to solving this phenomenon is called simply – BEETHOVEN. The same colossal musician who would influence the destinies of music and of all musicians from the first half of the 19th century and not only. How could we praise more appropriately the genius of the musician from Bonn, now when we celebrate 250 years from his birth, than through R. Wagner’s œuvre, who would identify himself with and consider himself a successor of Beethoven’s aesthetic and human ideals! I do not believe that the history of music can offer us a more eloquent example of artistic completion, all the more so since, paradoxically, the two great musicians never met.